Quality Evaluation of Selected Drug in Pharmaceutical Formulations by Spectrophotometric Estimation of Imatinib Mesylate in Pure and Tablet Dosage Form - Kumar Raja Jayavarapu; V. D. Sundar (Current Overview on Pharmaceutical Science Vol. 1, 2022)
For the determination of imatinib mesylate in both its pure and tablet dose forms, a simple and sensitive spectrophotometric approach has been established. Imatinib mesylate is a white crystalline powder. The suggested approach is founded on the measurement of ultraviolet light absorption in distilled water. The UV spectrum of Imatinib mesylate in distilled water showed \(λ\)max at 256 nm. Beer’s law is valid in the concentration range of 2-12 \(μ\)g/ml. In terms of precision, accuracy, ruggedness, and robustness, this method has been validated. The procedure is reproducible and selective for the estimation of the given drug, according to statistical analysis.